Kepribadian Narapidana dalam Tinjauan Model Big Five Personality - Tania Mayendry; Ahmad Hidayat; Juliarni Siregar (Journal An-Nafs: Kajian Penelitian Psikologi, 2019)
The purpose of this study was to describe the personality of prisoners in Bangkinang’s prison. The personality trait was assessed by Indonesian Big Five Inventory (BFI) that has been adapted by Ramdhani (2012) which consists of 44 items. Descriptive statistical analysis was used in this research. The result of this study shows that the highest mean score of personality trait is agreeableness (3.83) while neuroticsm has the lowest mean score (2.98). Based on the age range, all of the age range of the prisoner indicates that the most common trait is agreeableness (mean score 3.82 for 20-40 years old and 3.86 for 40-65 years old) while the lowest neuroticsm (mean score 3.00 for 20-40 years old and 2.98 for 40-65 years old). Analysis based on the type of offences shosw that the drugs and crime prisoners have agreeableness as the most trait (mean score 3.90 and 3.68) while the neuroticsm is the lowest (mean score 2.90 and 3.15).